Fontes e manejo de nitrogênio na cultura da batata em solos arenosos - Souza, Emerson de Freitas Cordova de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Potato plant (Solanum tuberosum L.) is one of the most grown species in the world. Nitrogen deficiency is one of the factors that limit this crop, because it is directly linked to the tuber yield. Thus, a study seeking the best strategy for the potato nitrogen utilization becomes necessary, mostly when it is grown in sandy soils. The objective of this work was to evaluate the behavior and chemical changes of soil after application of urea, ammonium sulfate and ammonium sulfonitrate, containing the nitrification inhibitor-DMPP, known commercially as Entec® 26; the effect of these sources and the nitrogen application rates on potato cropped in sandy soil, and more specifically, the effect of rates and split application of Entec on potato cropped in sandy soil. This way, a laboratory experiment in a completely randomized design, with four replications under constant temperature and humidity, and six experimental field, with four blocks in a randomized block design were carried out. The laboratory experiment had three fertilized treatments, (addition of Entec, ammonium sulfate, and urea) and one unfertilized as a control. For experiments I, II and III, a factorial design 3 x 3 + 1 was used. The treatments comprised three types of nitrogenous fertilizers applied (Entec, ammonium sulfate, and urea), as well as three rates of N (80, 120, and 160 kg ha-1) and one without nitrogen application as a control. On experiments IV, V, VI, the treatments comprised two rates (120 and 160 kg ha-1) of Entec fertilizer. It was either totally applied at planting or it was split applied (40 kg ha-1 at planting; remainder split applied). There was one unfertilized as a control. Urea increased the pH quickly and strongly, however, later on the pH decreased and promoted the greatest soil acidification. Besides, it was more nitrified than ammonium sulfate and Entec fertilizers. Entec kept the initial NO3- availability stable ...

A batateira (Solanum tuberosum L.) é uma das principais espécies vegetais cultivadas no mundo. No cultivo desta espécie, a deficiência de nitrogênio (N) é uma das que mais limitam o crescimento da planta, estando diretamente relacionada produção de tubérculos. Dessa forma, tornam-se necessários estudos que buscam a melhor estratégia para o melhor aproveitamento do N aplicado na cultura da batata, especialmente quando cultivada em solos arenosos. O objetivo deste trabalho foi avaliar o comportamento e as mudanças químicas do solo após a aplicação dos fertilizantes ureia, sulfato de amônio e sulfonitrato de amônio contendo o inibidor de nitrificação DMPP, comercialmente denominado Entec® 26; o efeito destas fontes e de doses de adubação nitrogenada na cultura da batata em solo arenoso e, especificamente o efeito de doses e do parcelamento do fertilizante Entec na cultura da batata cultivada em solo arenoso. Para isto foram realizados sete experimentos, um em laboratório conduzido sob condições controladas e seis outros em condições de campo. O delineamento experimental do experimento em laboratório foi inteiramente casualizado, com quatro repetições. Os tratamentos foram constituídos pela aplicação de três diferentes fertilizantes nitrogenados (Entec, sulfato de amônio e ureia) e um tratamento testemunha sem a aplicação de fertilizante. Nos experimentos I, II e III, o delineamento experimental utilizado foi o de blocos casualizados, no esquema fatorial 3 x 3 + 1, com quatro repetições. Os tratamentos foram constituídos por três fontes de N (Entec, sulfato de amônio e ureia), por três doses de N (80, 120 e 160 kg ha-1) e uma testemunha (sem aplicação de N). Nos experimentos IV, V e VI, o delineamento experimental utilizado foi o de blocos casualizados com quatro repetições. Os tratamentos foram compostos por duas doses (120 e 160 kg ha-1) do fertilizante ...
Sources and management of nitrogen on potato crop cultvated in sand soil
Keywords: Batata - Cultivo; Plantas - Nutrição; Plantas - Efeito dos minerais; Minerais na nutrição de plantas; Batata - Adubos e fertilizantes; Nitrogenio na agricultura; Nitrogen in agriculture